Union of the Comoros : Third Staff Review and Extension of the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2006)
This paper on the Third Staff Review and Extension of the Staff-Monitored Program for the Union of the Comoros reports that important structural reforms have been implemented in the fiscal area, but progress is slow in other areas and institutional capacity remained low. The authorities' macroeconomic program for 2006 focuses on securing the budgeted primary surplus of about 1 percent of GDP and avoiding new expenditure arrears. Tensions between the union and island governments have risen partly owing to a perceived weakening of coordination on fiscal policy.